Human Papillomavirus Type 33 Polymorphisms and High-Grade Squamous Intraepithelial Lesions of the Uterine Cervix - Khouadri, Soraya; Villa, Luisa L.; Gagnon, Simon; Koushik, Anita; Richardson, Harriet; Ferreira, Silvaneide; Tellier, Pierre; Simao, João; Matlashewski, Greg; Roger, Michel; Franco, Eduardo L.; Coutlée, Francois (The Journal of infectious diseases, 2006)
BackgroundWe investigated the association between polymorphisms of human papillomavirus (HPV)–33 and squamous intraepithelial lesions (SILs) MethodsEndocervical specimens from 89 women infected with HPV-33, out of a total of 5347 recruited for 2 case-control and 2 cohort studies, were further analyzed by polymerase chain reaction sequencing of the long control region (LCR), E6, and E7 ResultsOf the 89 samples, 64 were normal, 7 had low-grade SILs (including 3 determined by histopathologic analysis), 15 had high-grade SILs (HSILs, including 14 determined by histopathologic analysis), and 3 had an unknown diagnosis. Non–prototype-like LCR variants were significantly associated with HSILs (age- and study site–adjusted odds ratio [OR], 9.2 [95% confidence interval CI, 1.8–45.9]). The C7732G variation, which results in the loss of a putative binding site for the cellular upstream stimulatory factor, was associated with HSILs (age- and site-adjusted OR, 8.0 [95% CI, 1.5–42.8]). E6 and E7 polymorphisms were not associated with HSILs. Samples collected at 6-month intervals from 14 participants contained the same variant. The HPV-33 MT 1-0-0 variant carrying the G7584A variation was detected more frequently in women from Brazil (7/20 [35%]) than in women from Canada (1/65 [1.5%]; P=.001) ConclusionIntratypic LCR variants of HPV-33 seem to vary geographically and to differ with respect to their oncogenic potential